Your PDF contains multiple lecture PPTs from the GIAN course on Migration, Gender, Labour, and International Standards. The content spans historical, sociological, legal, and policy-oriented dimensions of migration. - Ganesh Satarkar (22667600) (2025)
GIVEN DETAILS – CLEAN & SIMPLE SUMMARY Your PDF contains multiple lecture PPTs from the GIAN course on Migration, Gender, Labour, and International Standards. The content spans historical, sociological, legal, and policy-oriented dimensions of migration. Below is a structured summary of the main sections from the file. 1. “Donkey Migration” – Illegal Migration from India Key Points “Donkey route” = illegal, unsafe migration path used to reach USA, Canada, Europe. Popular especially in Punjab & Haryana. Migrants depend on agents, middlemen, “donkers”, and criminal networks. Routes involve jungles, deserts, oceans (e.g., Darien Gap). Why People Choose Donkey Migration Low wages in India; high wage expectations. Unemployment, poverty, corruption. Strong aspiration for Western lifestyle. Coaching centers, media glorification. Agents create “dream selling”. Consequences Injury, death, exploitation, trafficking. No support when caught abroad. Loss of skilled youth from India. Diplomatic strains with destination countries. 2. Migration of Nurses from Punjab Global Context Worldwide nursing shortage. India = 2nd largest supplier of migrant nurses to OECD. Study Findings (303 nurses, Punjab) 66% had B.Sc Nursing. Starting salary in private hospitals: ₹4,000–5,000 only. Majority aspire to migrate to Australia, Canada, USA. 77% cite “better income & lifestyle” as reasons. Migration routes: Work permit (60%) Study visa / spouse visa as alternative Agents charge ₹15–30 lakh. Key Insight Nursing migration from Punjab is becoming a family strategy supported by networks and agents. 3. Gender & Migration – Feminist Perspectives Important Ideas Migration is gendered — women face different risks and opportunities. Women migrant workers mostly in informal sector: domestic work, manufacturing, services. High vulnerability to: Sexual exploitation Job loss Lack of social security Violence & harassment No written contracts ILO Convention 189 Protects domestic workers, including migrants: Safe working conditions Written contracts Social protection Protection from violence Access to complaint mechanisms 4. International Labour Standards (ILS) & Migration Key Conventions Migration for Employment Convention (C97) Migrant Workers Convention (C143) Private Employment Agencies Convention (C181) Domestic Workers Convention (C189) Focus Areas Equal treatment of migrant & national workers Prevention of trafficking, forced labour Social security protection Regulation of private recruitment agencies 5. Labour Codes of India – Migration Elements Occupational Safety, Health & Working Conditions Code (OSH Code) 2020 Expands definition of inter-state migrant worker. Provides: Toll-free helpline Portals and data collection Experience certificates Safety and health surveys Accommodation, crèche facilities Limitations Not fully gender-sensitive Implementation challenges Need for stronger protection for women migrants 6. Historical Context – Slavery & Indentured Labour Slavery Existed globally; reached peak in trans-Atlantic trade. 12.5 million Africans transported; 10.7 million survived. Indentured Labour After slavery ended, British transported ~2 million Indians (1834–1917) to: Mauritius Fiji Trinidad & Tobago South Africa Sri Lanka, Malaysia Conditions harsh; contracts misleading; high deaths on voyages. 7. South Asian Migration – Colonial & Contemporary Trends Colonial Era Labour migration: plantations, construction, military. Brokers/agents existed similar to today. Modern Era Massive migration to GCC: Saudi Arabia, UAE, Kuwait, Oman. South Asia has world’s largest diaspora (India: 17.7 million). Push factors: Unemployment Informal economy Low wages Pull factors: Gulf labour demand Western opportunities